Manajemen Pembelajaran Jarak Jauh pada Mata Pelajaran PAI dan BP SMP di Kota Tegal - Kurniawati, Indah; B.S, Abdul Wachid (QUALITY, 2021)
AbstractResearch on Distance Learning Management (PJJ) in the subject of Islamic Religious Education and Characteristics aims to identify distance learning management conducted on Islamic Education and BP SMP teachers in Tegal City. The distance learning management studied includes the Learning Management System (LMS) and PJJ Applications, the approaches and methods used, as well as the implications for competency attainment and the problems encountered. The Learning Management System and applications used are Google Classroom, WhatsApp, Google Form, Google Meeting, Zoom Cloud Meeting, and AGPAII Digital. The approach used is a scientific approach with the method of Problem Based Learning, Project Based Learning, Inquiry, and Discovery Learning. The implication of distance learning that is carried out is related to the achievement of students' competencies, including Attitude, Spiritual, Social, Knowledge and Skill Competencies. The training was carried out to overcome the problems faced, namely training on the use of LMS and PJJ applications, training on distance learning methods, and training on making ICT-based teaching materials. Effective communication with parents is needed in order to achieve competency attainment.AbstrakPenelitian Manajemen Pembelajaran Jarak Jauh (PJJ) pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti ini bertujuan untuk mengidentifikasi manajemen pembelajaran jarak jauh  yang dilakukan pada guru PAI dan BP SMP di Kota Tegal. Manajeman pembelajaran jarak jauh  yang diteliti meliputi Learning Management Sytem (LMS) dan Aplikasi PJJ, pendekatan dan metode yang digunakan, serta  implikasi terhadap ketercapaian kompetensi dan permasalahan yang ditemui. Learning Management Sytem dan aplikasi yang digunakan adalah Google Classroom, WhatsApp, Google Form, Google Meeting, Zoom Cloud Meeting, dan AGPAII Digital. Pendekatan yang digunakan adalah pendekatan saintifik dengan metode Problem Based Learning, Project Based Learning, Inquiry, dan Discovery Learning. Implikasi dari pembelajaran jarak jauh yang dilakukan berhubungan dengan ketercapaian kompetensi peserta didik, meliputi Kompetensi Sikap, yakni Spiritual dan Sosial, Pengetahuan, dan Ketrampilan. Pelatihan dilakukan untuk mengatasi permasalahan yang dihadapi, yaitu Pelatihan penggunaan LMS dan Aplikasi PJJ, Pelatihan metode pembelajaran jarak jauh, dan pelatihan pembuatan bahan ajar berbasis TIK. Komunikasi efektif dengan orang tua diperlukan guna mencapai ketercapaian kompetensi.